2021
DOI: 10.1177/1756284821993586
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier dysfunction in irritable bowel syndrome: a systematic review

Abstract: Background and Aim: Irritable bowel syndrome (IBS) is a complex and heterogeneous disorder. Sensory, motor and barrier dysfunctions are the key physiological endophenotypes of IBS. Our aim is to review studies evaluating barrier dysfunction in adults and children with IBS, as well as to link those changes with IBS symptomatology and quality of life. Methods: A comprehensive and systematic review of multiple databases was performed up to March 2020 to identify studies comparing intestinal permeability in IBS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 141 publications
(540 reference statements)
1
66
0
3
Order By: Relevance
“…The underlying mechanisms are still poorly understood, but several studies have demonstrated, using in vivo and ex vivo approaches, that altered intestinal permeability is associated with low-grade inflammation in all IBS subtypes. The primary mechanisms appear to be related to the regulation of tight and adherent junction proteins, OCLN in particular [ 78 , 79 ]. In a healthy context, OCLN is regulated by phosphorylation, but in IBS-D, it is dephosphorylated, which causes it to be internalized into the cytoplasm [ 78 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…The underlying mechanisms are still poorly understood, but several studies have demonstrated, using in vivo and ex vivo approaches, that altered intestinal permeability is associated with low-grade inflammation in all IBS subtypes. The primary mechanisms appear to be related to the regulation of tight and adherent junction proteins, OCLN in particular [ 78 , 79 ]. In a healthy context, OCLN is regulated by phosphorylation, but in IBS-D, it is dephosphorylated, which causes it to be internalized into the cytoplasm [ 78 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“… 38 Barrier dysfunction has been reported in 37–62% of adults with diarrhea-predominant IBS (IBS-D) and 4–25% of those with constipation-predominant IBS (IBS-C). 39 All four pediatric studies assessing the intestinal barrier in patients with IBS have demonstrated barrier dysfunction, which is associated with abdominal pain, symptom severity, depression, and anxiety. 39 …”
Section: Biopsychosocial Modelmentioning
confidence: 99%
“… 39 All four pediatric studies assessing the intestinal barrier in patients with IBS have demonstrated barrier dysfunction, which is associated with abdominal pain, symptom severity, depression, and anxiety. 39 …”
Section: Biopsychosocial Modelmentioning
confidence: 99%
“…Research on IBS has shown that changes in the microbiome contribute to motility disorders [18][19][20]. Patients with SIBO have different metabolomic profiles [21] as well as higher concentrations of lactate, acetate, and bile acids in comparison with control patients [22].…”
Section: Gut Microbiota and Intestinal Dysmotilitymentioning
confidence: 99%